Second Chance School: Designing and carrying out numeracy applications in ICT environments - Pipinos, Savas; Savvas, Ioannis (Συνέδρια της Ελληνικής Επιστημονικής Ένωσης Τεχνολογιών Πληροφορίας & Επικοινωνιών στην Εκπαίδευση, 2023)
Notions like literacy, multi-literacy and multimodality introduce another dimension in adult education. Under this perspective, the aim of this study is to propose ways to solve mathematical problems that arise naturally in the context of everyday life with the use of ICT, thus showing that it is possible to design and apply such methods in adult numeracy. We present the didactic procedure of an activity in a dynamic geometry environment that was performed in the school’s technology room with a sample of adult students, based on the principles of life long learning and in particular on a theoretical model by the New London Group.